The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18203/2394-6040.ijcmph20171327
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding sickle cell disease in adult sufferers and carriers in a rural area

Abstract: Background: According to State Health Society, there are about 30 lakhs sickle cell carrier and 1.5 lakhs sufferers in Maharashtra, prevalence being more in tribal population. As Sickle cell disease is associated with increased morbidity and mortality, it is important for patients to have awareness regarding its cause, treatment and genetic implication. To assess Knowledge, Attitude and Practices regarding sickle cell disease in adult sufferers and carriers. Materials and Methods: The present study is an cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…Patil SS et al, Coretta M et al and Treadwell M et al, reported lower proportion of knowledge compared to present study. 8,9,11 In the present study 78.64% study subjects agreed that there is need to take regularly treatment for sickle cell anaemia. Similar findings were reported by Olatano et al, Coretta et al and Kofi et al 12,9,10 In the present study, 29.12% (n=30) study subjects were aware about own sickle cell status and 23.3% (n=24) were aware about sickle cell status of their spouse.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Patil SS et al, Coretta M et al and Treadwell M et al, reported lower proportion of knowledge compared to present study. 8,9,11 In the present study 78.64% study subjects agreed that there is need to take regularly treatment for sickle cell anaemia. Similar findings were reported by Olatano et al, Coretta et al and Kofi et al 12,9,10 In the present study, 29.12% (n=30) study subjects were aware about own sickle cell status and 23.3% (n=24) were aware about sickle cell status of their spouse.…”
Section: Discussionmentioning
confidence: 46%
“…In present study, lower proportion of study subjects were aware about sickle cell status of their spouse. 8 Amongst the study subjects, about 19.41% agreed that there is need for pre-marietal screening of spouse for SCA. Similar findings were noted by Patil SS et al, Gamit C et al, Treadwell et a, Abd Nazir et al Knowledge towards premarietal screening of spouse for SCA was not good .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We used an interviewer administered questionnaire to determine awareness of SCT among study participants. The questionnaire was developed based on literature from the previous studies, 12 , 15 , 19 24 and pre-tested at St Benedict Medical Center in Mayuge District to check for clarity and comprehension. Following this, changes were made to suit the intended use.…”
Section: Methodsmentioning
confidence: 99%
“…Sickle cell disease (SCD) is an autosomal-recessive genetically transmitted haemoglobinopathy that is responsible for considerable morbidity and mortality. 1 Sickle cell disease results from a point mutation in the gene, a substitution of glutamic acid with valine at position six of the haemoglobin beta chain, causing an abnormality in haemoglobin synthesis, leading to the production of red blood cells that have an abnormal sickle shape. 2 The different forms of SCD include sickle cell anaemia (haemoglobin SS [HbSS]), sickle cell haemoglobin C (Hb-SC) and sickle cell thalassaemia (Hb-SSthal).…”
Section: Introductionmentioning
confidence: 99%